The Gap Between Service Excellence and Procedural Justice in Criminal Investigation Services at the West Jakarta Metro Police - Muhammad Rizky Ali Akbar; Agus Sumartomo (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Within the criminal justice system, investigative services serve as a critical arena where police legitimacy is shaped through citizens’ direct experiences, yet gaps between administrative compliance and public expectations often trigger dissatisfaction. This study aims to identify the implementation of service excellence in the criminal investigation process at the Criminal Investigation Unit (Satreskrim) of the West Jakarta Metro Police, to analyze complainants’ experiences of procedural justice, and to explain the gap between administrative service standards and public experience that may trigger complaints (Dumas). A qualitative case study approach was employed, with data collected through semi-structured interviews with 13 informants (investigators and complainants), document review, and observation. The findings indicate that while the unit demonstrates strong administrative compliance with standard operating procedures and criminal procedural law, a significant gap remains in interaction and communication between investigators and complainants. Within the A6 service excellence framework, ability and internal accountability function relatively well, whereas action and external accountability remain weak, particularly in inconsistent delivery of case progress updates and limited explanation of investigation delays. From a procedural justice perspective, this condition reduces complainants’ perceptions of trustworthiness and respect. This study concludes that Dumas is more often triggered by lack of process clarity (process-related complaints) than by dissatisfaction with case outcomes alone. Accordingly, improving investigative services requires enhancing the readability of case progress through scheduled, consistent, and substantive communication to strengthen procedural transparency and public trust.